Toward an urban soil health index: Emerging indicators for exposure, function, and resilience - Anna A. Paltseva; Shams Rahman Rahmani (Agricultural & Environmental Letters, 2026)
Abstract Urban soils are among the most dynamic and human‐impacted soil systems, yet most soil health frameworks remain rooted in agricultural assumptions, capturing fertility and structure while missing urban‐specific concerns: contaminant exposure, extreme heterogeneity, thermal stress, and degraded ecosystem services. This commentary proposes an expanded framework organized around three domains, exposure risk, ecosystem function, and physical resilience, and argues for broader adoption of six emerging indicator categories: heavy metal bioaccessibility, per‐ and polyfluoroalkyl substance, microplastics, soil thermal properties, ecosystem services, and antibiotic resistance genes. Each indicator should be normalized to a 0–1 scale and integrated into a composite urban soil health index calibrated to land use and management goals. Linking these urban‐specific metrics with established frameworks improves cross‐disciplinary continuity while acknowledging that cities require additional measures. A more complete indicator system can sharpen remediation priorities, guide urban planning, support food safety, and strengthen resilience in increasingly dense and climate‐stressed cities.